THE ROLE OF DIGITAL TECHNOLOGIES IN MODERN ACCOUNTING PRACTICES: CHALLENGES AND OPPORTUNITIES (Journal of Universal Science Research, 2024)
This article explores the integration of digital technologies into modern accounting practices. It examines the benefits, challenges, and opportunities associated with adopting technologies such as AI, blockchain, and cloud-based accounting systems. The study also highlights the evolving role of accountants in a digitalized environment. The findings are based on a literature review and a survey conducted among accounting professionals.